THE REVIEW OF OPENING PROCEDURES OF SHARIA BASED SAVING IN SHARIA FINANCIAL SERVICES COOPERATION BMT MITRA SADAYA BRANCH OF PURWAKARTA - Jalaludin, Jalaludin (Islamicate Institute, 2017)
This article describes the variation of syariah savings in the institution of the temple al-Maal wa al-Tamwil (BMT) Mitra sadaya. The approach used in this study is a qualitative approach and the type of data used in this study is descriptive. The object of this research is the analysis of the opening procedure of sharia savings at the institution of bait al-Maal wa al-Tamwil (BMT) Mitra Sadaya Purwakarta branch. The subject of the research is the source of data asked for the information according to the research problem. This study aims to determine the form of procedures, implementation procedures, the benefits of procedures and factors in running procedures in the opening of syariah savings. The results of this study are: Variations of Islamic savings at the institution of the temple al-Maal wa al-Tamwil (BMT) Mitra sadaya there are three contracts used: (1) principle akad wadi'ah, (2) Mudharabah contract principle, (3) Qard. Then for the opening procedure of syariah savings as follows: (1) Prospective customers / members come to the office or hold an appointment with marketing bait al-Maal wa al-Tamwil (BMT); (2) The prospective customer / member meets with the Customer Service section bait al-Maal wa al-Tamwil (BMT) Mitra sadaya; (3) Prospective customers / members fill out the application form of syariah account opening or savings account; (4) Prospective client / member shall sign the approval for opening of syariah saving account; (5) Entered and checked by the teller section; (6) Print sharia savings book in accordance with customer / member application; (7) The signing of officials related to the institution of al-Maal wa al-Tamwil (BMT) Mitra sadaya; (8) Calculate and give the first deposit money to the teller; (9) Input of initial deposit and deposit of deposit; (10) Re-check the nominal deposit with the amount of balance and stamp teller; (11) Account opening is completed and customers / members are welcome to go home. Shariah-compliant profit sharing of bait al-Maal wa al-Tamwil (BMT) Partners sadaya partner, if the form of ordinary sharia savings (other than deposits) gifts or profits are given equivalent to 35% of office income. However, if included in the category of gift deposits granted equivalent to 9% -13% per year. As well as deposits that fall into the category of capital of the institution of bait al-Maal wa al-Tamwil (BMT). Sadaya Partners that last from 4-5 years, the profits are equal to 30% -110%.